2018
DOI: 10.12927/hcq.2018.25709
|View full text |Cite
|
Sign up to set email alerts
|

Putting a Population Health Lens to Multimorbidity in Ontario

Abstract: Almost all Ontarians die with multimorbidity, and most accumulate more than five conditions over their lifetime. Our health system is still largely focused on specialties and treating one disease at a time-an approach that is incompatible with the healthcare needs of patients with multiple and often complex chronic conditions. This burden requires a health system that recognizes that patients will more likely live and die with multiple chronic conditions than not (i.e., multimorbidity management versus special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…This paper provides an overview of the needs of patients and clinicians in developing an integrated care model for patients with CCN and the needs of TM. Study findings revealed that significant gaps remain in meeting the needs of patients with CCN in current health care delivery practice [ 36 , 37 ]. Patients continue to navigate a fragmented care system [ 36 ] between primary care and siloed specialty care, creating challenges to timely access and care management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper provides an overview of the needs of patients and clinicians in developing an integrated care model for patients with CCN and the needs of TM. Study findings revealed that significant gaps remain in meeting the needs of patients with CCN in current health care delivery practice [ 36 , 37 ]. Patients continue to navigate a fragmented care system [ 36 ] between primary care and siloed specialty care, creating challenges to timely access and care management.…”
Section: Discussionmentioning
confidence: 99%
“…An integrated NP-led model of care focused specifically on patients with CCN would align with sustained calls for a common trajectory of multimorbidity and chronic disease management that focuses on patients from a more holistic and needs-based perspective [ 9 , 37 ]. Our findings suggest that a colocated model with a primary clinical contact can address the challenges faced by patients and clinicians in ambulatory care.…”
Section: Discussionmentioning
confidence: 99%
“…This approach holds promise for many health system applications. Patients with chronic diseases drive the majority of healthcare spending (Tinetti et al 2012), yet our healthcare and public health systems often take siloed approaches to chronic disease management and prevention (Rosella and Kornas 2018). For example, patients with diabetes are at risk for a wide range of complications including cardiovascular events, kidney disease and retinopathy.…”
Section: Potential For Health Services and Policymentioning
confidence: 99%
“…Given that survey data were not used, details on socio-demographics (e.g., immigration status, ethnicity), individual-level socioeconomic status (e.g., income, education), social support (e.g., living alone), or health behaviors (e.g., smoking, alcohol consumption, body weight) were not included. Therefore, there are opportunities to improve model performance by adding variables that are lacking in administrative data and creating a model that better informs population health approaches [ 39 ]. Furthermore, a model that allows for prediction at the population level contributes by allowing for accurate distribution of risk in the population, which can ensure that strategies for prevention are allocated to the populations that will most likely benefit from attention and outreach.…”
Section: Introductionmentioning
confidence: 99%